2022
DOI: 10.1016/j.ajhg.2021.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of gene regulation in Indonesian populations identifies QTLs associated with global and local ancestries

Abstract: Lack of diversity in human genomics limits our understanding of the genetic underpinnings of complex traits, hinders precision medicine, and contributes to health disparities. To map genetic effects on gene regulation in the underrepresented Indonesian population, we have integrated genotype, gene expression, and CpG methylation data from 115 participants across three island populations that capture the major sources of genomic diversity in the region. In a comparison with European datasets, we identify eQTLs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 89 publications
5
14
0
Order By: Relevance
“…DEPTOR, (59)). Overall, our ndings highlight regulatory effects on genes with key roles for human health, and add to a growing literature indicating the relatively high yield that can be provided by modest-sized studies on understudied populations (10,12,19).…”
Section: Discussionsupporting
confidence: 56%
“…DEPTOR, (59)). Overall, our ndings highlight regulatory effects on genes with key roles for human health, and add to a growing literature indicating the relatively high yield that can be provided by modest-sized studies on understudied populations (10,12,19).…”
Section: Discussionsupporting
confidence: 56%
“…In order to provide a more comprehensive understanding of the blood microbiome of remote populations within Indonesia, we analysed unmapped reads from previously-published whole blood transcriptomes, collected from 117 Indonesian individuals living on the islands of Mentawai (MTW) in western Indonesia, and Sumba (SMB) in central Indonesia, as well as the Korowai (KOR), a group living in the Indonesian side of New Guinea Island. The human samples have been extensively described [20, 21]. After extensive quality control, we obtained a mean library size of 8,146 taxonomically informative reads (range: 221 - 403,796), which was further reduced to 8,120 reads after the removal of singletons (range: 196 - 403,771; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This was true even for Korowai individuals with low levels of Apicomplexa abundance. Indeed, we have recently [21] identified rs13425622 as an eQTL that strongly impacts expression levels of MARCO in these populations (p = 3.10 × 10 −14 ). All Korowai individuals in our dataset are fixed for the minor G allele, which is associated with lower expression, while the majority of individuals from both Mentawai and Sumba are at least heterozygotes for the major T allele (Figure 4, D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying our approach to Neanderthal aSNPs segregating within present-day West Eurasians [ 31 ] replicates most of our findings, as well as previously reported signals including a depletion of Neanderthal variants within enhancer-like elements [ 12 ]. Previous studies have shown that, while polygenic risk scores [ 65 ] and eQTLs [ 66 ] have limited cross-population portability, biochemically active functional regulatory elements tend to be under evolutionary constraint within the human lineage [ 67 , 68 ]. Thus, while our approach is contingent on functional data generated in a population that is not of Papuan ancestry, our focus on functional analyses are likely to be more robust to differences across populations in linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 99%